Pusa Oishiki: New high yielding variety of brinjal - Saha, Parth; Munshi, A D; Behera, T K; Tomar, B S; Lyngdoh, Y A (Indian Horticulture, 2021)
Pusa Oishiki has been developed by hybridization (Pusa Purple Long Ã— DBL-21) followed by selection by the Division of Vegetable Science, ICAR-Indian Agricultural Research Institute, Pusa, New Delhi. This variety was identified for release in the XXXVII AICRP (VC) Group Meeting held at RARI, Durgapur, Jaipur, Rajasthan, 2018 for cultivation in zone VI (Rajasthan, Gujarat, Haryana and Delhi) and VII (Madhya Pradesh and Maharashtra) and notified by the Central Sub-Committee on crop standard, notification and release of varieties for Horticu ltural crops in 2019.